Traversing Sonic and Cyber Scapes: On Becoming a Tech Geek Girl. - Farrugia, Rebekah (Canadian Woman Studies)
Presents a personal narrative which explores the author's experience of traversing sonic and cyber scapes for many that has enabled her to no longer perceive technology-related projects and interests to be beyond the reach, and to fit into her own style.